Entrepreneurial Alertness and its role in enhancing strategic reputation: Analytical study in a sample of pharmacies in Dohuk governorate - Dashto, Nojan; Yousif , Mehvan (Humanities Journal of University of Zakho, 2022)
This research aims to determine the entrepreneurial alertness and its role in enhancing the strategic reputation. The pharmacies in Dohuk governorate were identified as a field for conducting the practical side. The research relied on the descriptive analytical approach, and it was also based on a set of main and secondary hypotheses that were field tested in the pharmacies surveyed, which numbered (330) Pharmacy and allowed (77) of those pharmacies to distribute the questionnaire to their pharmacists, and (109) pharmacists participated in the research, a questionnaire was relied on to collect data, and the data was analyzed using a set of statistical methods in the program (SPSS V.22) to analyze the correlation and effect between the research variables. The research reached a set of conclusions, the most important of which is the existence of a significant correlation between the dimensions of entrepreneurial alertness and strategic reputation, and the presence of a significant effect of entrepreneurial alertness with its dimensions on the strategic reputation of the pharmacies surveyed. Increasing attention to entrepreneurial alertness because of its role in enhancing strategic reputation and making it an integral part of its work.